The assessment of food security status: nutrient profiles, BMI and body composition status and habitual physical activity level among UiTM Puncak Alam students / Firdaus Abd Razak ... [et al.] - Abd Razak, Firdaus; Ismail, Hani Hamima; Sulaiman, Nurul'Azizah; Iskandar, Siti Nadiah (2014)
For the past fifty years, food security has become an alarming issue all over the world. A cross-sectional study was designed to investigate the prevalence of food security status among UiTM Puncak Alain students aged 18-25 as well as the assessment of nutrient profile (macronutrients and micronutrients), BMI and body composition and physical activity level between food secure and food insecure group. Guided self-administered questionnaires consist of demographic data. Adult Food Security Survey Module (AFSSM). food frequency questionnaire (FFQ) taken from "Kajian Pengambilan Makanan Malaysia 2002/2003" and computerized physical activity were answered by the participants. Anthropometric measurement includes body composition was also examined. For analysis data, compare means, independent t-test were used. A total of 52.5% of participants showed food secure whereas 47.5% showed food insecure. The results showed that some of the macronutrients and micronutrients intake met the RNI recommendations.